Transformation of Basic Education: The Effectiveness of the Integrated Thematic Approach on Students' Literacy and Numeracy Science - Amran, Muhammad; Sahabuddin, Erma Suryani (Journal of Education Reseach and Evaluation, 2025)
The current problem is the low level of literacy and numeracy science proficiency among Indonesian elementary school students, as indicated by various national assessment results. Based on this, the purpose of this study is to analyze the effectiveness of an integrated thematic approach in improving these basic skills among fifth-grade students. Using a quantitative approach, this study implemented a quasi-experimental method with an Unequal Control Group Design. The study involved a total of 60 fifth-grade students, who were divided into an experimental group and a control group, each consisting of 30 students. Data collection methods included pretests and posttests to assess literacy and numeracy skills, along with observations of learning activities and documentation of classroom teaching. Data analysis was conducted using an independent t-test to determine the statistical significance of differences in learning outcomes between the two groups. The findings showed a significant improvement in learning outcomes for the experimental group, with average scores in literacy and numeracy ranging from 16.6 to 17.4 points, compared to an increase of only 5.4 to 6.1 points for the control group. An independent t-test showed a statistically significant difference (p < 0.05) between the two groups. In conclusion, this study demonstrates that an integrated thematic approach is effective in improving literacy and numeracy competencies among elementary school students. Implementing such an approach can be beneficial in addressing the learning challenges faced by students in the 21st century.